The influence of serve speed on its efficiency in the example of the Estonian highest league volleyball team - Stamm, R.; Stamm, M.; Esna, A. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: This work aimed to find out which serve speeds have the greatest influence on ball reception. Do the balls hit the fastest are more difficult for the receivers of the ball to receive? METHODS: The research was carried out with the Selver/TalTech men`s volleyball team who is playing in the highest league in Estonia. There were 15 players (3 middle blockers, 6 outside hitters, 3 setters, 1 opposite hitter, 2 liberos) aged 17 to 30 years and their mean height was 191 cm and mean weight was 80,26 kg. Altogether 818 serve speeds were measured together with the reception quality of the opponents during 10 matches in the Baltic League in 2022. Serve speed was measured by Pocket Radar SD2000 and the reception efficiency using the 5 balls scale according to the Data Volley program. RESULTS: From the 818 served serves 61 went to the direct points (aces) and with the mistake ended 109 serves. The maximum speed of the serves was 109 km/h and the minimum speed was 42 km/h. Maximum speed was reached twice- once by the middle blocker and once by an outside hitter. The best ball reception scores were achieved by receiving the slowest serves. CONCLUSION: The following conclusions can be drawn from the analyzed results: The success rate of inaccurate reception of the ball is increasing compared to the increase in the speed of the serve. We divided the serve speeds by standard deviation into three different classes (fast serves, medium serves, and slow serves) and compared slow serve receptions with fast serve receptions efficiency by mean values. And can conclude after the students` t-test that the efficiency for the receptions that followed the fast serves was statistically significantly lower than the receptions efficiency that followed slow serves (p<0,01). The highest number of direct serve errors were made at the fastest serve speed, so the faster the serve, the higher the probability of a direct serve error. This agrees with Mercelino`s work (Mercelino et al., 2008) which concluded that better teams are gathering the mistakes during the serves more, but they succeeded in earning direct points also more often. The authors think that we still must take risks with high-speed serving because as Paulo`s research concluded the direct points earned by the serves are correlated with winning the matches. (Paulo et al., 2017)